Logistic process improvement of applying SLP, 5S, and slotting in the main warehouse of a hydroelectric power plant - Álvarez Calleja, Gilda Nicida (2023)
The main warehouse of a hydroelectric plant is crucial for managing the spare parts necessary for equipment maintenance. However, its inefficient use can generate costs and decrease logistical efficiency. To improve this situation, solutions based on engineering tools such as SLP, 5S, and Slotting were proposed. The pilot implementation showed an 89% increase in the utilization of storage space indicator (UCA), a 40.73% reduction in lead time, and a 10.18% decrease in inventory level. These tools had a significant impact on space optimization, reduction in search times, improvement in inventory management, and reduction in operating costs. Consequently, they improved efficiency, profitability, and satisfaction in the logistical management of the hydroelectric plant.